Hubungan Frekuensi Minuman Kemasan Berpemanis dengan Status Gizi pada Remaja Usia 13 - 15 Tahun di SMP Muhammadiyah 1 Surakarta - Rini Anggita; Nur Lathifah Mardiyati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The consumption of sweetened beverages (SVB) is increasing among adolescents and is thought to contribute to nutritional status problems, both overnutrition and undernutrition. Adolescents who frequently consume sweetened beverages tend to experience an increase in daily calorie intake without being balanced appropriate energy needs, so they are at risk of being overweight. This study aims to determine the relationship between the frequency of consumption of sweetened beverages and nutritional status in adolescents aged 13-15 years at Muhammadiyah 1 Junior High School, Surakarta. The purpose of this study was to determine the relationship between the frequency of consumption of sweetened beverages and nutritional status in adolescents aged 13-15 years at Muhammadiyah 1 Junior High School, Surakarta. This study used an observational analytical study design with a cross-sectional approach. The sample was 77 students consisting of several classes, namely grades VII, VIII and IX. Data on the frequency of consumption of sweetened beverages was collected using a Quantitative Food Frequency Questionnaire for the past 1 month, while nutritional status was determined based on body mass index using WHO standards. In the analysis of students of Muhammadiyah 1 Junior High School Surakarta, 5.1% were found to be undernourished, 36.3% to be overnourished, and 9% to be obese. The analysis showed that adolescents consumed sweetened packaged drinks in the category of sometimes 15.5%, and often 27.2%. After being analyzed using statistical tests, namely the Chi Square test, there was a relationship between the frequency of sweetened packaged drinks and nutritional status (p = 0.039).